INFLUENCE DIVERSITY OF PRODUCTS, PRICE, PROMOTION AND LOCATION TOWARDS CUSTOMER SATISFACTION WITH PURCHASE DECISION AT TRANSMART CARREFOUR PLAZA MEDAN FAIR - Syilvana Dwi Novianti (AXIOM : Jurnal Pendidikan dan Matematika, 2019)
The research aims to know and identify: (1) The positive influence of product diversity on purchasing decisions, (2) The positive influence of price diversity on consumer buying decisions, (3) positive influence on the promotion of decisions Consumer Purchase, (4) positive influence of location against consumer purchase decisions, (5) positive influence of product diversity to consumer satisfaction through consumer buying decisions, (6) positive influence of price diversity towards consumer satisfaction Through consumer purchase decisions, (7) positive influence of promotion to consumer satisfaction through consumer purchase decisions, (8) positive influence of location towards consumer satisfaction through consumer buying decisions, and (9) positive influence Decision to purchase customer satisfaction. Research conducted at the Transmart Carrefour Plaza Medan Fair. Types of research is quantitative research with research methods is a survey method. The population in this research is the consumer Transmart Carrefour Plaza Medan Fair as much as 100 respondents. The data collection instruments used are polls. The analysis of the data used is path analysis. Research findings Show: (1) There is a positive influence of product diversity on consumer purchasing decisions with a coefficient of 0.204 so that it can be determined that a variation of 20.40% in the purchase decision is decided by Diversity of products, (2) there is a positive influence on the price diversity of consumer purchasing decisions with a coefficient of 0.297, so that it can be determined that a variation of 29.70% on the purchase decision is defined by a diversity of prices, (3) There is a positive influence on the promotion to the consumer purchase decision with a coefficient of 0.175, so it can be determined that a variation of 17.50% on the purchase decision set by the promotion, (4) there is a positive influence of location To the consumer purchase decision with a coefficient of 0.327, so it can be determined that a variation of 32.70% on the purchase decision is defined by an easily accessible location factor, (5) There is a positive influence of product diversity to customer satisfaction through a consumer purchase decision with a coefficient of 0.128 so that it can be determined that a variation of 12.80% on consumer satisfaction is defined by factors Product diversity through consideration of the purchasing decision factor, (6) There is a positive influence of price diversity towards consumer satisfaction through the decision of consumer purchase by coefficient. Amounting to 0.148 so that it can be determined that a variation of 14.80% on consumer satisfaction is defined by the price diversity factor through consideration of the purchase decision Factor, (7) there is a positive influence promotion to customer satisfaction Through a consumer purchase decision with a coefficient of 0.157 so that it can be determined that a variation of 15.70% on consumer satisfaction is defined by the promotion factor through consideration of the purchasing decision factor, (8) There is a positive influence on location to customer satisfaction through the decision of consumer purchase with a coefficient of 0.114 so that it can be determined that a variation of 11.40% in consumer satisfaction is defined by the location factor through Decision factor considerations, and (9) there is a positive influence on purchasing decisions positively affect the customer satisfaction with a coefficient of 0.548 so that it can be interpreted that there is a variation of 54.80% on satisfaction Determined by the purchasing decision factor.